2017
DOI: 10.1039/c7tx00083a
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of hydrophilic phosphine hexanuclear rhenium cluster complexes’ toxicity

Abstract: This article evaluates the link between ligands on rhenium clusters and their toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Octahedral rhenium cluster complexes of the general formula [{Re6Q8}L6] n (where Q is S or Se, and L are either inorganic or organic terminal ligands) and related cluster-based materials have attracted significant attention of researchers due to the unique combination of properties that they possess. This includes phosphorescence in the red/near-infrared region upon UV/blue light excitation [1][2][3][4][5][6], electroluminescence [7], their ability to generate singlet oxygen [8][9][10] and high X-ray attenuation efficacy [11][12]. This set of properties opens an avenue to applications such as materials for light emitted diodes [7], photoactive liquid crystals [13][14], optical bioimaging [9][10][15][16], photodynamic therapy [10], imaging agents for X-ray computed tomography [11][12] and others [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Octahedral rhenium cluster complexes of the general formula [{Re6Q8}L6] n (where Q is S or Se, and L are either inorganic or organic terminal ligands) and related cluster-based materials have attracted significant attention of researchers due to the unique combination of properties that they possess. This includes phosphorescence in the red/near-infrared region upon UV/blue light excitation [1][2][3][4][5][6], electroluminescence [7], their ability to generate singlet oxygen [8][9][10] and high X-ray attenuation efficacy [11][12]. This set of properties opens an avenue to applications such as materials for light emitted diodes [7], photoactive liquid crystals [13][14], optical bioimaging [9][10][15][16], photodynamic therapy [10], imaging agents for X-ray computed tomography [11][12] and others [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the family of octahedral cluster complexes [{Re 6 Q 8 }L 6 ] and [{Mo 6 X 8 }L 6 ] (where X is Cl, Br or I; Q is S, Se or Te and L are organic or inorganic ligands) and materials based on them have been intensively studied in the last few years in the context of biomedical applications. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] First of all, this is due to the progress made in the develop-ment of phosphorescent octahedral molybdenum cluster complexes, all based on the {Mo 6 I 8 } 4+ cluster core that have particularly high quantum yields [34][35][36][37] and high efficiency in generating singlet oxygen. [38][39][40][41][42][43] Specifically, our recent studies have shown that materials doped using {Mo 6 I 8 } 4+ are highly photoluminescent and have low cellular toxicity in the dark, while by a careful selection of a matrix the cellular internalisation and photoinduced toxicity of the materials can be tuned.…”
Section: Introductionmentioning
confidence: 99%
“…as imaging and photodynamic therapeutic agents) [11] and biology as bioimaging and biolabeling agents. [12][13][14][15] Unlike the related photoluminescent hexarhenium cluster complexes [16][17][18][19][20], the major "bottleneck" issue that hinders the direct application of the hexamolybdenum clusters in biomedical applications is poor solubility in water of the majority of known cluster complexes. To explore the great potential of the octahedral molybdenum cluster complexes in biomedical applications, research so far was mostly focused on the development of the hybrid materials based on inert inorganic [8,21,22] or organic [23][24][25][26][27] matrices.…”
Section: Introductionmentioning
confidence: 99%